2020
DOI: 10.1371/journal.ppat.1008953
|View full text |Cite
|
Sign up to set email alerts
|

YebC regulates variable surface antigen VlsE expression and is required for host immune evasion in Borrelia burgdorferi

Abstract: Borrelia burgdorferi , the Lyme disease pathogen causes persistent infection by evading the host immune response. Differential expression of the surface-exposed lipoprotein VlsE that undergoes antigenic variation is a key immune evasion strategy employed by B . burgdorferi . Most studies focused on the mechanism of VlsE antigen variation, but little is known about VlsE regulation and factor(s) that regulates differential vlsE expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…TPANIC_0474 is highly homologous (51% identical, 73% similar) to the Borrelia burgdorferi YebC/PmpR family DNA binding transcriptional regulator (BB0025) that affects the expression levels of VlsE, a B . burgdorferi surface lipoprotein involved in immune evasion [ 41 ]. In our studies, more TPANIC_0474 transcripts were detected in T .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPANIC_0474 is highly homologous (51% identical, 73% similar) to the Borrelia burgdorferi YebC/PmpR family DNA binding transcriptional regulator (BB0025) that affects the expression levels of VlsE, a B . burgdorferi surface lipoprotein involved in immune evasion [ 41 ]. In our studies, more TPANIC_0474 transcripts were detected in T .…”
Section: Resultsmentioning
confidence: 99%
“…One gene that had significantly higher transcript levels in infected rabbits was the transcriptional regulator yebC . Zhang et al [ 41 ] found that mutation of yebC in B . burgdorferi resulted in differences in transcript levels in 32 genes, with the largest decrease occurring in the antigenic variation protein gene vlsE .…”
Section: Discussionmentioning
confidence: 99%
“…This potential redundancy in function would be limited by the distinct onset-dependent production of these proteins: in immunocompetent mice, ospC expression begins after ticks feed and is downregulated shortly after B . burgdorferi disseminates, whereas the expression levels of vlsE are regulated by YebC [ 43 ] and are not significant until later, when spirochete dissemination occurs [ 44 , 45 ]. Nevertheless, in a SCID mouse, which lacks the adaptive immune response that is ordinarily countered by the hypervariable VlsE, persistent infectivity of a VlsE-deficient, but not a VlsE + B .…”
Section: Discussionmentioning
confidence: 99%
“…However, BadR lacks the SDRs found in NagC, Mlc, and other ROK repressors, consistent with the observation that the DNA-binding of recombinant BadR was not affected by phosphorylated sugars (Ouyang and Zhou, 2015), and the expression of genes involved in GlcNAc transport and utilization were not affected in the badR mutant (Miller et al, 2013), supporting that BadR does not function analogously to NagC or Mlc and is yet another example of an atypical transcriptional regulator influencing the expression of enzootic cycle-specific genes (Samuels and Radolf, 2009). YebC YebC ( BB0025) is a transcription factor that belongs to a putative YebC/PmpR family of DNA-binding transcriptional regulators (TACO1 family, pfam PF01709) (Shin et al, 2002;Zhang et al, 2012) and controls vlsE expression (Zhang et al, 2020). VlsE undergoes antigenic variation in the vertebrate host and vlsE expression increases concomitantly with the decrease in ospC expression in response to the host adaptive immune response, but there are few mechanistic details on the regulation of vlsE expression (Norris, 2014;Chaconas et al, 2020).…”
Section: Badrmentioning
confidence: 94%
“…VlsE undergoes antigenic variation in the vertebrate host and vlsE expression increases concomitantly with the decrease in ospC expression in response to the host adaptive immune response, but there are few mechanistic details on the regulation of vlsE expression (Norris, 2014;Chaconas et al, 2020). Zhang et al (2020) very recently demonstrated that deletion of yebC dramatically reduced vlsE mRNA levels in vitro. Expression of yebC and vlsE is coregulated in response to culture temperature, and is inversely regulated with expression of ospC during vertebrate infection.…”
Section: Badrmentioning
confidence: 99%